Not Your Parents’ Internationalization: Next Generation Perspectives - Rumbley, Laura; Proctor, Douglas (International Higher Education, 2018)
Although still young, internationalization of higher education has provided the stimulus for a burgeoning field of research, with concentrations in English speaking countries in the global North. New perspectives are now coming to the fore, exploring alternative contexts, topics, and methods in internationalization, and giving rise to the voice of a next generation of researchers.